Quantitative endoscopy in the chemoprevention of Barrett’s Esophagus Trial - Shar, A. O. (2008)
The Chemoprevention for Barrett’s Esophagus Trial (CBET) was a phase IIb, multicenter, randomized, placebo-controlled trial of celecoxib in patients with Barrett’s esophagus. The overall outcome of the study was that there were no significant differences in primary, secondary, or tertiary outcomes. The purpose of the current study is to focus on results related to the method of measuring lesion size called quantitative endoscopy (QE). The design includes a review of a total number of studies and then restricts analyses to the four clinics that enrolled more than four patients each for whom a baseline and 1-year QE study was performed, comparing intra- and inter-patient and clinic differences in Barrett’s esophagus. Measurements include the number of total QEs and adverse events, changes in areas from baseline to 1 year and other intervals, classification of Barrett’s lesion type with respect to patients, clinics, and treatment. A total of 309 QE studies were completed with no adverse events. Differences in surface area measurements over time for a particular patient are smaller than the differences for randomly selected patients. The complexity mix (as defined by the mix of circumferential, tongues, and islands) of the Barrett’s lesions varied with different clinics. In conclusion, QE is an efficient, safe, and accurate way to measure the area of Barrett’s lesions variation between different clinical sites may be attributable to a subtle type of selection bias at the individual clinics rather than to regional differences.